The implementation of collaborative network for innovation process in higher education institutions (heis): a knowledge management perspective - Selamat, Md. Hafiz; Ahmad @ Sharif, Mohd. Nazir; Miskon, Suraya; Eri, Zeti Darleena (Faculty of Computer Science and Information System, 2006)
The Implementation of Collaborative Network for Innovation Process in Higher Education Institutions (HEIs): A Knowledge Management Perspective. The scopes of this study are (1) to produce a computer-supported collaborative working model to support the innovation processes in higher education institutions which concentrate on the knowledge sharing perspectives, (2) to develop a mechanism of collaborative innovation in term of knowledge communication among research group, (3) To identify the roles of information technology in collaborative working environment specifically in research and development activities from the knowledge management perspective. The steps of the study are (1) Preliminary Study, (2) Literature Review, (3) Data collection, (4) Design, (5) Development and testing. The expected result are (1) A collaborative networking model for knowledge management to assist research activities mainly among researcher in HEIs, (2) A prototype of knowledge management systems based on the proposed model, (3) Results from the evaluation of knowledge management systems prototype.